Pengaruh Kemalisme Terhadap Undang-Undang Poligami di Turki - Nur Kamilia (Al-Adl : Jurnal Hukum, 2023)
This paper aims to discuss the issu of the influence of Kemalism on the polygamy law in Turkey to disribe universally the influence of Kemalism on the polygamy law in Turkey by firs knowing Mustafa Kemal’s mission in the information of a republic there. This paper will try to answer haw Kemalism has a major influence on the family law, especially the polygami law. this paper includes the results of the qualitatif research with data sources and documents from a  number og books and articels as well as as from other data sources related to this paper. The result of this paper is to find a complete overhaul of state regulations regarding the family right in 1917 in which it is explained that polygamy is not prohibited but still on condition that the husband can be fair to his wives and the wafe may write a divorce not before the marriage after this (polygamy). If the man ignores this, than the divorce has the right to be carried out into the Turkish Civil Code of 1926, which explains the absolute prohibition of polygamy. This cange occurred because of the influence of Kemalism on the Turkish state. From this infuence there is rule regarding violations againts people who practice polygamy. However, there are no rules that explicitly regulate sanctions for such violation The Turkish Family Law Of Cyprus 1951. But basically the lawimplicitly exsplain that polygamy in Turkey is not permitted and those who violate it will get a penalty.